Trichothecene Genotypes of the Fusarium graminearum Species Complex Isolated from Brazilian Wheat Grains by Conventional and Quantitative PCR - Tralamazza, Sabina M.; Braghini, Raquel; Corrêa, Benedito (Frontiers in Microbiology, 2016)
We compared two well-established methods, fungal isolation followed by conventional PCR and DNA analysis by quantitative PCR (qPCR), to define trichothecene genotypes in Brazilian wheat grains from different locations. For this purpose, after fungal isolation from 75 wheat samples, 100 isolates of the Fusarium graminearum species complex (FGSC) were genotyped by PCR to establish their trichothecene profile. For profiling by qPCR, DNA was extracted from the wheat samples and analyzed. The methods provided similar and divergent results. The FGSC isolates were classified as NIV (55%), 15-ADON (43%), and 3-ADON (2%). Analysis by qPCR showed 100% contamination with 15-ADON strains in all wheat samples, 80% contamination with the NIV genotype, and only 33.3% contamination with 3-ADON strains. Further analysis revealed that 96% of all quantified DNA was attributed to the 15-ADON profile, while 3.4% was attributed to NIV and only 0.06% to 3-ADON. A positive correlation was observed between 15-ADON genotype DNA concentration and deoxynivalenol (DON) content in the wheat samples. The high frequency of fungi, DNA levels and positive correlation with DON strongly indicate that 15-ADON producers are the main trichothecene genotype in Brazilian wheat grains. Surprisingly, although many isolates (55%) carried the NIV genotype and this genotype was identified in 80% of the wheat samples, only 3.4% of fungal DNA was in fact from NIV producers. Although, our findings showed that each method provided a different perspective about the trichothecene profile, DNA analysis by qPCR gave us new insight about fungal contamination levels in Brazilian wheat grains. Nevertheless, both techniques should be used to obtain more robust results.